Aryl hydrocarbon receptor‐driven signals inhibit collagen synthesis in the gut. Issue 4 (5th February 2016) - Monteleone, Ivan; Zorzi, Francesca; Marafini, Irene; Di Fusco, Davide; Dinallo, Vincenzo; Caruso, Roberta; Izzo, Roberta; Franzè, Eleonora; Colantoni, Alfredo; Pallone, Francesco; Monteleone, Giovanni
Abstract : Fibrostrictures are a major complication and indication for surgery in Crohn's disease (CD). Aryl hydrocarbon receptor (AhR), a member of the Per‐ARNT‐Sim superfamily proteins, regulates several genes involved during fibrosis in liver and lung. TGF‐β1 and TNF‐α increased collagen secretion in CD fibroblasts and this effect was reduced by Ficz, an activator of AhR. Ficz treated mice were largely protected from trinitrobenzene‐sulfonic‐acid induced fibrosis and showed a marked downregulation of collagen production. AhR is a negative regulator of profibrotic signals in the gut. Abstract : Fibrostrictures (FS) are a major complication of Crohn's disease (CD). Pathogenesis of FS is not fully understood, but activation of fibroblasts and excessive collagen deposition are crucial in the development of FS. Here, we investigated the role of aryl hydrocarbon receptor (AhR) in intestinal fibrosis. AhR RNA and protein expression were evaluated in intestinal fibroblasts of CD patients and controls. CD fibroblasts were stimulated with TGF‐β1 or TNF‐α in the presence or absence of the AhR activator Ficz, an AhR antagonist CH223191, or a specific AhR‐silencing RNA. In CD fibroblasts, TGF‐β1 and TNF‐α increased Col1A1, Col3A1 and α‐SMA transcripts and collagen secretion and this effect was reduced by Ficz and upregulated by CH22319. TGF‐β1 or TNF‐α induced activation of p38 and ERK1/2 MAP kinases was decreased by Ficz and increased by CH223191. The inhibitory effect of Ficz on Map kinase activation and collagen induction was abolished by AhR silencing. To assess the role of AhR in vivo, mice with trinitrobenzene‐sulfonic‐acid induced colonic fibrosis were given Ficz or CH223191. Mice given either Ficz or CH223191 produced less or more collagen respectively as compared with control mice. Our results indicate that AhR is a negative regulator of profibrotic signals in the gut.